2018
DOI: 10.1177/1934578x1801300415
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Shoot Cultures of Pterospartum tridentatum as an Alternative to Wild Plants as a Source of Bioactive Compounds

Abstract: The aim of this study was to evaluate the composition of aqueous extracts of in vitro shoot cultures and wild plants of Pterospartum tridentatum in order to promote the use of this plant material as a possible source of bioactive compounds. The extraction yield from wild plants compared with in vitro shoot cultures was lower. The total phenolic contents of in vitro shoots were significantly lower compared with those of wild plants. The phenolic profiles of in vitro shoots were very similar to those of wild pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 15 publications
2
12
1
Order By: Relevance
“…In both cases our data are in accordance with the previous reported [14,33,39,40]. The presence of taxifolin glucosides in this species, in particular taxifolin 6-C-glucoside [8,33], was also reported. In this study taxifolin glucosides were found in all extracts, the compounds eluted at 8.59, 8.74, and 9.24 min (Table 1).…”
Section: Flavonol and Flavanonol Derivativessupporting
confidence: 93%
See 4 more Smart Citations
“…In both cases our data are in accordance with the previous reported [14,33,39,40]. The presence of taxifolin glucosides in this species, in particular taxifolin 6-C-glucoside [8,33], was also reported. In this study taxifolin glucosides were found in all extracts, the compounds eluted at 8.59, 8.74, and 9.24 min (Table 1).…”
Section: Flavonol and Flavanonol Derivativessupporting
confidence: 93%
“…Apparently, this is the first report on their occurrence in this species, however their natural occurrence is well reported and our data are in accordance with the previously reported data, which were also used to establish our assignment [35][36][37][38]. Myricetin 6-C-glucoside (Figure 8), assigned to the compound eluted at 10.89 min, was previously found in the G. tridentata extract [14,33], as well as isorhamnetin 3-O-glucoside (Figure 8), assigned to the compound eluted at 10.89 min. [39].…”
Section: Flavonol and Flavanonol Derivativessupporting
confidence: 92%
See 3 more Smart Citations